(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The results of experimental studies of the molybdenum impurity influence on corrosion and mechanical properties of carbon steel (Grade 20) joint welds are presented in the article. In particular, it has been found that the highest and stable values of the impact strength and resistance properties of cracks (К1s and δs), as well as the resistance to sulfide corrosion cracking of the metal of tubular steel joints, are achieved at a concentration of molybdenum in it from 0,2 to 0,4%, which is realized by putting a molybdenum powder in the electrode coating in the amount of 0,5-1,0%. On the basis of the obtained results an optimal chemical composition of the weld metal was determined which is characterized by a fine-grained structure with a small amount of non-metallic impurities of globular shape. Optimal content of the doping micro-additive - molybdenum should be selected, based on both the influence of molybdenum on the size of structural components, but, most importantly, on its effect on the corrosion and mechanical properties of metal joint weld.